Expression Analysis of the Transporters of Sinorhizobium Meliloti - Sartor, Andrea L. (My University, 2006)
Sinorhizobium meliloti is an alpha-proteobacterium that forms symbiotic nodules on the roots of Medicago sativa (alfalfa). The ability to catabolize specific compounds available in the soil is one of the best-characterized factors to increase competition for nodulation. In order to successfully attain symbiosis S. meliloti must compete for nutrients in the rhizosphere, which can be done by having a large number of transport systems encoded in its genome. Genes encoding proteins involved in transport constitute the largest (12%) class of genes in the S. meliloti genome. Great interest now lies in determining substrates for the transport systems and their role in the survival and fitness of S. meliloti.
An estimated 824 transport genes in the genome of the soil bacterium Sinorhizobium meliloti are predicted to encode 382 transport systems. All of the S. meliloti transporters had been studied under 120 different conditions, including growth on various carbon and nitrogen sources, seed and root exudates and starvation conditions.
From this screen of every transport system in S. meliloti, the substrates that induce expression of over 50 transport systems have been identified. We have found putative transporters for amino acids, sugars, sugar alcohols, amino sugars, betaines and other compounds that might be found in the soil. This large scale expression analysis gives insight into the natural environment of S. meliloti by studying those genes that are induced by compounds that would be found in the soil.
Keywords: expression analysis, transporters, Sinorhizobium meliloti, alpha-proteobacterium, nodulation, compounds, soil